Investigation of acoustic and vibrational properties using Laser Doppler Vibrometry (LDV) and Electronic Speckle Pattern Interferometry (ESPI) of the kulintangan instruments - Hamdan, Sinin; Musib, Ahmad Faudzi; Mohamad Said, Khairul Anwar; Othman, Saiful Hairi; Sawawi, Marini (Universiti Putra Malaysia Press, 2023)
This study visualises the mode of the vibration of kulintangan using Electronic Speckle Pattern Interferometry (ESPI) to reveal the modes. It was found that the production of sound by the kulintangan was dominated by a particular mode which may be the (0,1), (1,1), (2,2), (3,2), and (4,2) of free edge circular gong. The spectrum distribution from the strike on the kulintangan showed it. The small gong A-H has an approximately harmonic spectrum with a fundamental frequency of 1240, 1055, 934, 792, 705, 624, 474, and 422 Hz. The gong does not display a similar occurrence of harmonics due to the ruggedness of the surface texture of the gong. This finding can be of great importance to facilitate a better understanding of the mechanisms involved in the sound production of musical instruments. Our research is visualising the sound sonically through PicoScope oscilloscopes and ESPI.